Analisis Faktor-Faktor yang Mempengaruhi Minat Nasabah terhadap Produk Cicil Emas sebagai Investasi Jangka Panjang di Bank Muamalat Purwokerto - Novika Nur Fitriana; Ismiati Ismiati; Pandu Kurniawan; Sulasih Sulasih (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to examine various factors that influence customers' engagement in choosing the Cicil Emas product as a form of long-term investment at Bank Muamalat Purwokerto. This research is based on the increasing trend of gold investment in the community caused by the increase in gold prices and awareness of the importance of halal investment according to sharia principles. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of Bank Muamalat Purwokerto. The results show that customer interest is influenced by several main factors, namely trust in sharia principles through the murabahah contract, a positive perception of gold as a stable investment asset, the ease of installment procedures that are flat and transparent, and the efficiency of the payment system through autodebit. In addition, social factors such as family recommendations and active promotions from the marketing department also strengthen customer interest. From the SWOT analysis, it was found that the main strength of this product lies in Bank Muamalat's reputation as a pioneering sharia bank and a stable installment system, while its main weaknesses are limited physical gold stocks and low public investment literacy. With increasing public awareness of sharia investment and the large market potential in Purwokerto, the Cicil Emas product has strong prospects for continued growth as a safe and Islamically-compliant long-term investment instrument.